Challenges in exercising the right to annual leave for workers on long-term sick leave in the Republic of Croatia - Bjelić-Gaćeša Dragana (Zbornik Radova Pravnog Fakulteta u Nišu)
The right to paid annual leave is one of the fundamental rights in the employment relationship. As such, it is incorporated in a number of legal acts, both at the international and regional, as well as at the national levels. The purpose of this right is to enable the workers to rest from physical and/or mental work, to enable them to enjoy relaxation and leisure in order to restore their working abilities. In accordance with the case law of the Court of Justice of the European Union (CJEU), the right to paid annual leave is a particularly important principle of the Community social law; thus, it must be granted to every worker regardless of his/her health status. However, in the Republic of Croatia, the workers who have been on long-term sick leave may face significant difficulties in exercising their right to paid annual leave after returning to work. Pursuant to Article 84 of the applicable Croatian Labour Act, on carrying over the annual leave to the next calendar year, a worker who, due to illness, does not use annual leave in full or in part in the calendar year in which it was earned, is entitled to use it upon returning to work, but no later than 30 June of the following calendar year. The question arises how a worker who has spent two, three or more years on long-term sick leave will fit into this provision. Will this legal solution deprive the worker of the right to paid annual leave? The aim of the paper is to analyse the relevant provisions of the Croatian positive law concerning the right to paid annual leave and the possibility of transfer it to it to the next calendar year over, to correlation them with the relevant European directives and judgments of the Court of Justice of the EU, to draw conclusions on their compliance with EU law, and discuss their impact on the position of workers and employers in the Republic of Croatia.